Standardized rearing process of the black soldier fly (Hermetia illucens) under marginal conditions for bioprospecting purposes - Ospina-Yepes, Juan Pablo; García-Trejo, Juan Fernando; Hurtado-Salazar, Alejandro; Ceballos-Aguirre, Nelson (Revista de Ciencias Agrícolas, 2024)
There is growing interest in large-scale breeding of black soldier fly (BSF) larvae due to their ability to consume a wide variety of organic materials. This study aimed to standardize the key developmental phases of Hermetia illucens within a rearing unit under marginal conditions (2160 meters above sea level; Temperature 14 °C average annual precipitation of 1800 mm) in an Andean Temperate Forest ecosystem. The primary objective was to optimize the production of 5-day-old larvae. A subdivided plot design was employed, incorporating two cage types, three attractants types, two glasses and three egg-laying sites, with three replicates for each combination, resulting in a total of 108 experimental units. The following factors were compared: cage type (Zurbrügg type cage and a cage proposed by the University of Caldas), attractant (organic waste, fermented waste, and a mixture containing 100 grams of dead black soldier fly adults), drinkers (cotton and sponge) and egg-laying sites (three different dimensions (A: 45 cm x 12 cm x 7 cm, B: 24 cm x 7 cm x 3 cm, and C: 12 cm x 1.2 cm x 0.5 cm)The combination of the University of Caldas cage, sponge drinkers, and the type C attractant yielded the most promising results in terms of egg weight and projected larval population size under the specific marginal conditions of the study area. The findings of this study will help to promote strategies to transform organic waste using BSF larvae in marginal conditions.